Missions aériennes de reconnaissance au Groenland 1957-1958. - Bauer, A.; Baussart, M.; Carbonnell, M.; Kasser, P.; Perroud, P.; Renaud, A. (Meddelelser om Grønland, 1968)
The present report on the air reconnaissance flights in Greenland gives a detailed account of research carried out in 195? and 1958 in preparation of the main EGIG-expedition of 1959- 1960. Due to the air reconnaissances and direct observations it has been possible to draw the crevassed areas on the west side of the Greenland ice sheet, to delimit the catchment-basin of the large glaciers between 68 and 72° N, and to determine the annual velocity of the ice sheet by photointerpretation of the intervals between large crevasses. The operations of 1958 give an account of the work of setting up ablation stakes and tests of coring for dating by Tritium. To measure the mean velocity at the front of the glaciers, a new technique in taking repeated aerial photographs without preparation in the field proved to be very successful. The detailed working out of these aerial photographs by Institut Geographique National is given. The velocities of the 20 glaciers between 68 and 72° N have been measured. The mean velocity at the front varies between 0,9 and 13,1 m/24 h. The solid discharge of all outflow glaciers is estimated to be 90 ± 10 % km3/year of ice. This discharge is clearly larger than previous estimations values, which strenghten the conclusion that the mass balance of the whole Greenland ice sheet is negative. Different transverse profiles of velocity show a clear acceleration of the flow of the glaciers towards their front where it reaches its maximum.